MeasureIce: accessible on-the-fly measurement of ice thickness in cryo-electron microscopy - Hamish G. Brown; Eric Hanssen (Communications Biology, 2022)
MeasureIce is an ice thickness measurement tool for screening and selecting acquisition areas of cryo-EM grids.